Low-temperature wafer-scale growth of MoS 2 -graphene heterostructures - Kim, Hyeong U.; Kim, Mansu; Jin, Yinhua; Hyeon, Yuhwan; Kim, Ki Seok; An, Byeong Seon; Yang, Cheol Woong; Kanade, Vinit; Moon, Ji Yun; Yeom, Geun Yong; Whang, Dongmok; Lee, Jae Hyun; et al. (Applied Surface Science, 2019)
In this study, we successfully demonstrate the fabrication of a MoS 2 -graphene heterostructure (MGH) on a 4 inch wafer at 300 °C by depositing a thin Mo film seed layer on graphene followed by sulfurization using H 2 S plasma. By utilizing Raman spectroscopy and high-resolution transmission electron microscopy, we have confirmed that 5–6 MoS 2 layers with a large density of sulfur vacancies are grown uniformly on the entire substrate. The chemical composition of MoS 2 on graphene was evaluated by X-ray photoelectron spectroscopy, which confirmed the atomic ratio of Mo to S to be 1:1.78, which is much lower than the stoichiometric value of 2 from standard MoS 2 . To exploit the properties of the nanocrystalline and defective MGH film obtained in our process, we have utilized it as a catalyst for hydrodesulfurization and as an electrocatalyst for the hydrogen evolution reaction. Compared to MoS 2 grown on an amorphous SiO 2 substrate, the MGH has smaller onset potential and Tafel slope, indicating its enhanced catalytic performance. Our practical growth approach can be applied to other two-dimensional crystals, which are potentially used in a wide range of applications such as electronic devices and catalysis.
Keywords: Catalytic performance; Chemical compositions; Electronic device; Hydrogen evolution reactions; Large-scale; MoS2; Nanocrystallines; Two-dimensional crystals; Graphene; Heterostructure; Hydrogen evolution reaction; Large-scale; MoS 2; PECVD